2019
DOI: 10.1074/jbc.ra118.006166
|View full text |Cite
|
Sign up to set email alerts
|

4-Methylumbelliferyl glucuronide contributes to hyaluronan synthesis inhibition

Abstract: Edited by Peter Cresswell 4-Methylumbelliferone (4-MU) inhibits hyaluronan (HA) synthesis and is an approved drug used for managing biliary spasm. However, rapid and efficient glucuronidation is thought to limit its utility for systemically inhibiting HA synthesis. In particular, 4-MU in mice has a short half-life, causing most of the drug to be present as the metabolite 4-methylumbelliferyl glucuronide (4-MUG), which makes it remarkable that 4-MU is effective at all. We report here that 4-MUG contributes to H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
31
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 40 publications
(31 citation statements)
references
References 45 publications
0
31
0
Order By: Relevance
“…Another doubt is the low bioavailability and short half-life of 4-MU; in a recent study its main metabolite 4-MUG was found to contribute to the bioactivity of 4-MU both in vitro and in vivo via conversion to 4-MU. 42 This conversion was observed in cell cultures after 48-72 hours 42 ; this may explain why the 24-hour 4-MUG treatment in our study was not sufficient to exert any effect on OFs and DFs.…”
Section: Discussionmentioning
confidence: 62%
“…Another doubt is the low bioavailability and short half-life of 4-MU; in a recent study its main metabolite 4-MUG was found to contribute to the bioactivity of 4-MU both in vitro and in vivo via conversion to 4-MU. 42 This conversion was observed in cell cultures after 48-72 hours 42 ; this may explain why the 24-hour 4-MUG treatment in our study was not sufficient to exert any effect on OFs and DFs.…”
Section: Discussionmentioning
confidence: 62%
“…In this work, we considered that the effects of 4-Mu are due to the inhibition of HA-synthesis. 4-Mu is a highly specific inhibitor, and it is unlikely to affect any key pathways other than HA synthesis ( Nakamura et al, 1995 ; Kakizaki et al, 2004 ; Kultti et al, 2009 ; Nagy et al, 2019 ). However, we cannot excluded the possibility that 4-Mu might be affecting other targets that control the sequential formation of molars.…”
Section: Discussionmentioning
confidence: 99%
“…4-MU is a fluorescent derivative of coumarin widely used in experimental conditions to specifically inhibit HA production both in vitro and in vivo models. 31,79-82 Although the mechanism of action is still under debate, some evidences demonstrated that 4-MU is metabolized to 4-MU-glucuronide (4-MUG) functioning as a competitive substrate for UDP-glucuronosyltransferase (UGT) with the consequent decline of UDP-GlcUA concentration and HA levels. 83 Other mechanisms proposed are based on HAS2 and HAS3 inhibition, 83 as well on UPP and dehydrogenase (UGDH) mRNA reduction.…”
Section: Metabolic Inhibition Of Ha Synthesis By 4-mumentioning
confidence: 99%